The Wiley Blackwell Encyclopedia of Race, Ethnicity, and Nationalism 2015
DOI: 10.1002/9781118663202.wberen153
|View full text |Cite
|
Sign up to set email alerts
|

Football Hooliganism

Abstract: Few phenomena in contemporary society have elicited such strong sentiments as that labeled “football hooliganism.” The disorder and violence that the phrase encapsulates has been studied, policed, and legislated against from a wide variety of starting points. In this entry the authors contend that the epiphenomena provoked by hooliganism are as worthy of academic inquiry as the “hooligans” themselves. The entry charts the history of football hooliganism as well as of governmental and academic responses to it, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Armstrong and Testa's (2010) exploration of Italy's neo-fascist UltraS (hardcore soccer supporters) revealed that their soccer loyalties were a subplot to their wider ideological allegiances that were disseminated in the stadium, a de facto 21st century agora (Greek: "meeting place") for the fans. Elsewhere in Egypt and Turkey, Dorsey (2013) has explored the role ultras play in political protests and has argued that "hooligan" acts must be situated in the context of wider political loyalties and complex sociopolitical machinations (Armstrong and Rosbrook Thompson, 2015). As Coakley and Pike (2009) postulate, "Sports events do not occur in a social vacuum.…”
Section: Hooliganism: They Thought It Was All Overmentioning
confidence: 99%
See 4 more Smart Citations
“…Armstrong and Testa's (2010) exploration of Italy's neo-fascist UltraS (hardcore soccer supporters) revealed that their soccer loyalties were a subplot to their wider ideological allegiances that were disseminated in the stadium, a de facto 21st century agora (Greek: "meeting place") for the fans. Elsewhere in Egypt and Turkey, Dorsey (2013) has explored the role ultras play in political protests and has argued that "hooligan" acts must be situated in the context of wider political loyalties and complex sociopolitical machinations (Armstrong and Rosbrook Thompson, 2015). As Coakley and Pike (2009) postulate, "Sports events do not occur in a social vacuum.…”
Section: Hooliganism: They Thought It Was All Overmentioning
confidence: 99%
“…As a result, the phenomenon has lost its "British" correlate and as the scope for exploration has become international, the locus of analysis has shifted from strictly soccer-related violence to dynamics and agendas far more complex than the impulse to confront rival fans (Armstrong and Rosbrook-Thompson, 2015). Armstrong and Testa's (2010) exploration of Italy's neo-fascist UltraS (hardcore soccer supporters) revealed that their soccer loyalties were a subplot to their wider ideological allegiances that were disseminated in the stadium, a de facto 21st century agora (Greek: "meeting place") for the fans.…”
Section: Hooliganism: They Thought It Was All Overmentioning
confidence: 99%
See 3 more Smart Citations